Planning and Development of INROLL Noodle Business as an Innovation of Instant Noodle-Based Snacks among the Younger Generation - Tarigan, Alexandria Oktavianta Emeia; Shofa, Hikmah Mardiana; Shani, Nayla Nahdiya; Wulandari, Wanda; Aini, Laila Nur; Rosyada, Trias Amrina; Ikaningtyas, Maharani (Indonesian Journal Publisher, 2025)
This study aims to examine the planning and development process of an innovative culinary business called Mie Gulung (INROLL), based on instant noodles and targeted at the younger generation. INROLL is presented as a modern snack that combines the familiar taste of instant noodles with an aesthetic appearance and appealing toppings such as cheese, nori, and beef slices. The method used is descriptive qualitative with a literature study and SWOT analysis approach. The results indicate that product innovation, attractive visuals, affordable pricing, and digital marketing strategies via social media are key factors in attracting young consumers. However, challenges remain, such as negative perceptions of instant noodles, short shelf life, and potential inconsistencies in product quality. With the right development strategies, including content-based promotion and collaboration with influencers, INROLL has great potential to become a new snack trend favored by millennials and Gen Z.